Nrf2 protects human alveolar epithelial cells against injury induced by influenza A virus - Kosmider, Beata (BioMed Central, 2012)
BACKGROUND: Influenza A virus (IAV) infection primarily targets respiratory epithelial cells and produces clinical outcomes ranging from mild upper respiratory infection to severe pneumonia. Recent studies have shown the importance of lung antioxidant defense systems against injury by IAV. Nuclear factor-erythroid 2 related factor 2 (Nrf2) activates the majority of antioxidant genes. METHODS: Alveolar type II (ATII) cells and alveolar macrophages (AM) were isolated from human lungs not suitable for transplantation and donated for medical research. In some studies ATII cells were transdifferentiated to alveolar type I-like (ATI-like) cells. Alveolar epithelial cells were infected with A/PR/8/34 (PR8) virus. We analyzed PR8 virus production, influenza A nucleoprotein levels, ROS generation and expression of antiviral genes. Immunocytofluorescence was used to determine Nrf2 translocation and western blotting to detect Nrf2, HO-1 and caspase 1 and 3 cleavage. We also analyzed ingestion of PR8 virus infected apoptotic ATII cells by AM, cytokine levels by ELISA, glutathione levels, necrosis and apoptosis by TUNEL assay. Moreover, we determined the critical importance of Nrf2 using adenovirus Nrf2 (AdNrf2) or Nrf2 siRNA to overexpress or knockdown Nrf2, respectively. RESULTS: We found that IAV induced oxidative stress, cytotoxicity and apoptosis in ATI-like and ATII cells. We also found that AM can ingest PR8 virus-induced apoptotic ATII cells (efferocytosis) but not viable cells, whereas ATII cells did not ingest these apoptotic cells. PR8 virus increased ROS production, Nrf2, HO-1, Mx1 and OAS1 expression and Nrf2 translocation to the nucleus. Nrf2 knockdown with siRNA sensitized ATI-like cells and ATII cells to injury induced by IAV and overexpression of Nrf2 with AdNrf2 protected these cells. Furthermore, Nrf2 overexpression followed by infection with PR8 virus decreased virus replication, influenza A nucleoprotein expression, antiviral response and oxidative stress. However, AdNrf2 did not increase IFN-λ1 (IL-29) levels. CONCLUSIONS: Our results indicate that IAV induces alveolar epithelial injury and that Nrf2 protects these cells from the cytopathic effects of IAV likely by increasing the expression of antioxidant genes. Identifying the pathways involved in protecting cells from injury during influenza infection may be particularly important for developing new therapeutic strategies.